Production of cocoa butter substitute via enzymatic interesterification of fully hydrogenated palm kernel oil, coconut oil and fully hydrogenated palm stearin blends - Ornla-Ied, Pimwalan; Rungsang, Sirinapa; Tan, Chin Ping; Lan, Dongming; Wang, Yonghua; Sonwai, Sopark (Japan Oil Chemists' Society, 2022)
Abstract: This research synthesized structure lipids (SL) from blends of fully hydrogenated palm kernel oil (FHPKO), coconut oil (CNO) and fully hydrogenated palm stearin (FHPS) by enzymatic interesterification (EIE)using rProROL, an sn-1,3-specific lipase from Rhizopus oryzae, as a catalyst. Five physical blends of FHPKO:CNO:FHPS were prepared with the following wt. ratios: 40:10:50, 50:10:40, 60:10:30, 70:10:20 and 80:10:10. The EIE reactions were carried out at 60℃ for 6 h in a batch-type reactor using rProROL 10% wt. of the substrate. It was found that EIE significantly modified the triacylglycerol compositions of the fat blends resulting in changes in the crystallization and melting behavior. In particular, SL obtained from EIE of blend 70:10:20 exhibited high potential to be used as a cocoa butter substitute (CBS) because it showed similar solid fat content curve to the commercial CBS and crystallized into fine spherulites and desirable β′ polymorph.